Contact Laws for Rough Surfaces - Willner, Kai (Zeitschrift für angewandte Mathematik und Mechanik, 2000)
Contact laws for rough surfaces are used to obtain e.g. contact stiffness or contact conductivity. Usually contact laws are derived on the basis of asperity deformation models in conjunction with a stochastic roughness model. As the stochastic parameters depend strongly on the measurement procedure, the obtained contact laws have to be used carefully. Fractal surface parameters can be obtained, which are independent of sampling interval or length, but the resulting contact laws are still dependent on these values.
UnivIS-Import:2015-04-16:Pub.2000.tech.FT.FT-TM.contac